Computer modeling of complex dynamic systems. Assessment of the need for specialists. - Сениченков, Юрий Борисович; Рыжов, Владимир Александрович; Шорников, Юрий Владимирович; Доставалов, Дмитрий Николаевич (Computer Tools in Education, 2017)
.